Openness to experience predicts intrinsic value shifts after deliberating one's own death. Issue 4 (21st April 2018) - Prentice, Mike; Kasser, Tim; Sheldon, Kennon M.
ABSTRACT: Individual differences that might moderate processes of value shifting during and after deliberating one's own death remain largely unexplored. Two studies measured participants' openness and relative intrinsic-to-extrinsic value orientation (RIEVO) before randomly assigning them to conditions in which they wrote about their own death or dental pain for 6 days, after which RIEVO was assessed again up to 12 days later. When participants confronted thoughts about their own death over a sustained period, high openness to experience helped them shift toward intrinsic values. Implications for understanding openness' role in value reorientation from existential deliberation processes are discussed.